Trafficking, acidification, and growth factor signaling - Niehrs, Christof; Boutros, Michael (Science signaling, 2010)
Wnt and Notch signaling pathways play key roles in development and disease. Despite great progress, the mechanism of signal transduction of their receptor-ligand complexes still holds surprises. For example, in both pathways, endocytosis is required for downstream signaling, but the mechanism by which endocytosis permits signaling is still unknown. New evidence indicates that endocytosis is required for the receptor-ligand complex to reach an acidified vesicular compartment. In turn, enzymes responsible for acidification are essential for Notch and Wnt signaling and also directly interact with the receptors. These findings raise new questions concerning the mechanism by which low pH promotes signal transduction and may open new possibilities for therapeutic intervention through the targeting of acidifying enzymes.